Infrastructure Development and Conflict: A Conflict Resolution in The Construction of An Oil Refinery - Nisa, Desinta Roichanun; Sihidi, Iradhad Taqwa (Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
The construction of an oil refinery in Tuban Regency, a National Strategic Project (PSN), has been rejected by the Tuban community. This study aims to explain the efforts made by PT Pertamina and the government in resolving the land acquisition conflict regarding the construction of an oil refinery in Jenu, Tuban Regency. The researchers used the descriptive qualitative method, collected data using interviews and documentation, and analyzed the collected, reduced and presented data. The results showed that the parties resolved the conflict through litigation, mediation, and negotiation. The process resulted in the provision of employment for locals, scholarships for outstanding students in five affected villages, development of fishermen's cooperatives in Mentoso Village, food and social assistance for farmers, opportunities for locals to continue working on the acquired land before the construction, and several Corporate Social Responsibility (CSR) programs around the premises. After the resolution, out of 1219 parcels, 1222 were acquired with a total land area of 814 hectares from 961 owners. This research only focuses on the agreements between the parties. Further studies are advised to observe PT Pertamina's and the community's consistency in adhering to the agreements.